THE EFFECTIVENESS OF CHILD-FRIENDLY SCHOOLS ON THE CHARACTER OF LEARNERS - Syahroni Syahroni; Sowiyah Sowiyah; Hasan Hariri (International Journal Labs, 2022)
Background: The effectiveness of child-friendly schools on the character of students attracted the author's interest in conducting a literature review. The implementation of education aims to educate and improve the lives of children in order to become human beings who are faithful, pious, responsible, noble, happy, and prosperous in accordance with human rights. Child-friendly schools as institutions that respect children's right to education, health, protection from violence and discrimination. Objective: This study aims to obtain a theoretical foundation that can be used to support problem solving related to the effectiveness of child-friendly schools on the character of learners. Methods: The research method used is a literature review. This literature review aims to obtain a theoretical foundation that can be used to support problem solving related to the effectiveness of child-friendly schools on the character of students. The results of the study of child-friendly schools show that child-friendly schools have an impact on building positive character for students. Child-friendly schools provide space for students without discrimination to develop their potential and talents in order to realize character education. Results: The results of a study of child-friendly schools showed that child-friendly schools had an impact on building positive character for didi k participants. Conslusion: Child-friendly schools provide space for students without discrimination to develop their potential and talents in order to realize character education. The hope of developing this potential without discrimination is that students have good character to become students who have faith and piety, are critical, creative and responsible.